Prisec II: A comprehensive model for IoT security - Costa, P.; Noetzold, D.; García Ovejero, R.; Martín Esteban, R.; Leithardt, V. (Proceedings of the 5th Int. Conference on Disruptive Technologies, Tech Ethics and Artificial Intelligence (DiTTEt 2025), 2025)
This study examines data security and efficiency in interconnected IoT devices, focusing on selecting cryptographic algorithms to improve secure data transmission in 5G networks. The proposed model introduces four security levels, each applying different encryption strategies to balance security and performance. Cloud computing is integrated to mitigate computational limitations in IoT devices, optimizing encryption and decryption processes. The study evaluates multiple cryptographic algorithms, analyzing encryption and decryption times, packet throughput, and memory usage. Experimental results demonstrate that the model enables efficient encryption while maintaining security, with AES-256 and XChaCha20 showing stable performance across different packet sizes. The cloud-based implementation improves resource distribution and reduces processing delays. This work contributes a structured cryptographic model adaptable to varying security needs and a performance evaluation of different cryptographic approaches in cloud-integrated environments.